A comparative study of diode-clamped and cascaded H-bridge in multilevel inverter for harmonic reduction - Mohammed Rasheed, Jubair (2014)
This dissertation presents a comparative study of two types of multilevel inverters that comprise of diode clamped and cascaded H-Bridge multilevel inverter for reduction of harmonics in the multilevel inverter output. The proposed system is designed using MATLAB/SIMULINK and it consists of diode clamped and cascaded H-Bridge multilevel inverters. The controller is based on the pulse width modulation (PWM) technique which is applied to the purposed three phase multilevel inverters. The various performances of simulation results of the diode clamped and cascaded H-Bridge multilevel inverters were investigated. The Total harmonic distortion (THDv) of the output voltage was measured for the two types of multilevel inverters. Based on varying simulation results, it has been found that the THD voltage of the H-Bridge multilevel inverter is considerably lower than the diode clamped multilevel inverter.